Digital technology practices for vocational teachers in the industrial revolution 4.0: Mediating technology self-efficacy - Choyrul Anwar; Herminarto Sofyan; Nani Ratnaningsih; Muh. Asriadi AM (Journal of Pedagogical Research, 2024)
The efficacy of vocational teachers' utilisation of digital technology in the context of the Industrial Revolution 4.0 remains a pressing concern that necessitates pragmatic resolutions. Social support and infrastructure are the leading causes of the limited technological self-efficacy of digital technology practices. This research seeks to examine the impact of infrastructure and social support through technological self-efficacy on vocational teachers' digital technology practices during the Industrial Revolution 4.0. The research employed a quantitative approach and ex-post-facto methods, involving 207 vocational teacher respondents. The data was analysed using structural equation modelling techniques, namely path analysis and bootstrapping approaches. The inquiry results indicate that technological self-efficacy acts as a mediator of digital technology practices, with a statistically significant p-value of less than .05. The relationship between social support for digital technology practices and technology self-efficacy is mediated by an estimate of 0.089 with a p-value of .019. Similarly, the relationship between infrastructure for digital technology practices and technology self-efficacy is mediated by an estimate of 0.250 with a p-value of .000. A comprehensive analysis of variables, including their direct, indirect, and total effects, revealed a considerable influence of the variables included in the study. After analysing the features of each respondent, a p-value < .05 was achieved, indicating a significant influence between the variables evaluated. It suggests that the relationship between the variables can be broadly applied to the characteristics of each respondent. Enhancing digital technology practices in vocational education requires increased efforts from educational institutions and the government.